ROLE OF GREEN INTELLECTUAL CAPITAL INDEX TO CARBON EMISSION DISCLOSURE AND TRANSPARENCY ON FINANCIAL PERFORMANCES - Riki Sanjaya Tjan; Regina Jansen Arsjah (International Journal of Contemporary Accounting, 2023)
The purpose of this research is to examines the effect of carbon emission disclosure and transparency on financial performance moderated by the green intellectual capital index. The objects of this study are energy, transportation, logistics, and banking industries sector of public listing companies during period 2020-2022 at IDX. 188 companies (the sample of this research) selected with purposive sampling and analyzed using multiple regression. Secondary Data used in this research, the example stock price, sustainability, financial and annual reports. Eviews is used as statistical software. This research has some results, they are show that carbon emission disclosure influence negatively to financial performance, but that result is different with the using of the green intellectual capital index as the moderating variable (factor) that resulted in the carbon emission disclosure had a positive effect on financial performance, and type of industry had a influence positively to financial performance. This research has some implications for stakeholders, especially for regulators and governments that conduct multiple socializations to the public about the urgency of carbon emission disclosure in order to improve public environmental consciousness and for companies to encourage the activities regarding the reduction of carbon emission (also disclose the carbon emissions reduction at their reports) with improved capability environmental aspect or green intellectual capital.